CASE REPORT: FEBRILE SEIZURES - Betty Nuning Widyaningsih (Faculty of Medicine, Public Health, and Nursing, 2018)
.......Cases of febrile seizures mostly occur in children but people still often do not understand how to deal with fever and febrile seizures.Problems experienced by patients involved the need for management of the febrile seizures immediately, carefully and precisely and with consideration of the patient’s safety. In addition, health workers are expected to respond to parents' worries about the 'sequelae' of the febrile seizures.........